Sensing strain and damage in polyurethane/MWCNT nano-composite foams using electrical measurements - A. Baltopoulos; N. Athanasopoulos; I. Fotiou; A. Vavouliotis; V. Kostopoulos (eXPRESS Polymer Letters)
This work deals with the damage identification in polymeric foams through the monitoring of the electrical resistance of the system. To assess this idea electrically conductive rigid Poly-Urethane (PUR) foams at various densities were prepared. Multi-Wall Carbon Nanotubes (MWCNT) were dispersed in the host polymer at various concentrations through high shear mixing to provide electrical conductivity to the system. The PUR/MWCNT foams exhibited varying electrical conductivity on a wide range of densities and nano-filler contents. The prepared foams were subject to compression tests. Electrical resistance was recorded online during the tests to monitor the change of the bulk property of the materials. A structural-electrical cross-property relation was exhibited. The distinctive phases of foam compression were successfully identified from the electrical resistance profile recorded during the tests. A characteristic master curve of the change of electrical resistivity with respect to load and damage is proposed and analyzed. It was shown that the found electrical resistance profile is a characteristic of all the MWCNT contents and depends on density and conductivity. MWCNT content contributes mainly to the sensitivity of electrical sensing in the initial stage of compression. Later compression stages are dominated by foam microstructural damage which mask any effect of CNT dispersion. Micro-structural observations were employed to verify the experimental findings and curves.